Keragaman dan Intensitas Kutu Parasit (Ordo: Phthiraptera) pada Ayam Kampung (Gallus gallus domesticus) - imam widhiono; Viola Firstrianti Salsabila; edy riwidiharso riwidiharso (Fakultas Biologi Universitas Jenderal Soedirman, 2021)
Abstract Phthiraptera lice is the common ectoparasite that attacks domestic chickens. Parasitic lice infestation is not lethal, but it can seriously disrupt the growth of chickens. The purpose of this study was to determine the diversity of lice species infecting domestic chickens in five villages in Purwokerto and its surroundings and to determine the infestation intensity of each species of lice infecting the body parts of domestic chickens in five villages in Purwokerto and its surroundings. This research was conducted using survey method and random sampling techniques in five villages in Purwokerto and its surroundings, namely Kedungwuluh Village, Kedungwringin Village, Kutasari Village, Karangsalam Village, and Karanggintung Village. Lice were sampled from five female and male domestic chickens in each village. Lice sampling is carried out on the head, wings, thighs, chest and legs of the chickens. Lice samples were then observed and identified under a microscope in the Laboratory of Entomology and Parasitology, Faculty of Biology, Unsoed. Lice sample data found in chickens from each location and body part were analyzed for variance using software SPSS 16 and using the Shannon-Wiener diversity index. The identification results showed that there were three species of lice species (order Phthiraptera) which were found infesting domestic chickens (Gallus gallus domesticus) in five villages in Purwokerto and its surroundings, namely Menopon gallinae, Lipeurus caponis, and Menacanthus cornutus. The three species of lice were the member of two families (Menoponidae and Philopteridae). Species diversity based on the Shannon-Wiener diversity index shows location I (H´: 0.914), location II (H´: 0.693), location III (H´: 1.066), location IV (H´: 1.081), and location V (H ´: 0.878). Interpretation from all sites indicated that sites I, III, and V had low species diversity, while sites II and IV had moderate species diversity. The intensity of lice infestation on domestic chickens (Gallus gallus domesticus) was 16.82%. The intensity of each type of lice in domestic chickens (Gallus gallus domesticus) was M. cornutus (32%), M. gallinae (30,9%), and L. caponis (21,2%).